Metaphorical Figurative Language in Literature: A Translation Perspective - Ainun Fatimah; Muhammad Nur Iman; Kamsinah Kamsinah (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This paper is motivated by the existence of the novel The Secret History (1992, 2010) which is rich in meaning and recognized as one of the important and influential literary works. The purpose of this research is to show the dominant type of figurative language used in the novel. This research was conducted by identifying and classifying the use of figurative language consisting of (1) metaphor, (2) idiom, (3) hyperbole, (4) verbal irony, (5) indirect request, and (6) contextual expression (Colston, 2015). The findings of the study show that this novel is dominated by the use of metaphor, while contextual expression has the least occurrence. This finding is consistent with the hypothesis that humans use metaphors six times per minute in conversation, indicating that the use of figurative language in this novel not only enriches the narrative but also reflects broader human communication patterns. Thus, this study contributes to the understanding of the role of figurative language in literature and its impact on readers.